(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Employee turnover is a growing challenge for organizations in emerging economies, where retaining skilled professionals is critical to performance. This study investigates the key factors influencing employees’ intention to leave their jobs in Tashkent, Uzbekistan. Using a quantitative approach, the research examines the relationships between turnover intention and several organizational variables, including job satisfaction, job stress, salary, training and development, performance, and organizational commitment. A structured questionnaire was administered to 380 employees, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that job stress, salary, and training & development are positively correlated with turnover intention, while job satisfaction has a strong negative relationship. Surprisingly, organizational commitment and performance were not significant predictors. The findings highlight the importance of job satisfaction and work environment in designing effective employee retention strategies.